24/7 Neighbourhood Mental Health Centres: early lessons from Birmingham, UK - S. P. Sashidharan; Selvaraj Vincent; Fabida Aria (The British Journal of Psychiatry, 2026)
Summary The editorial presents early lessons from Birmingham’s 24/7 Neighbourhood Mental Health Centre, one of six national pilots, as an alternative to the current fragmented system of community mental healthcare. Early data suggest that the model is feasible and has positive outcomes while emphasising that transformation depends on fidelity, investment and full implementation.